Perancangan Sistem Informasi Pemesanan Menu Berbasis Web Di Kedai Warbi - Isqi Nurrahman; Muhammad Rizki Yahya; Novita Febriyani Putri (CV. Multi Kreasi Media, 2023)
Design of a web-based menu ordering information system at Kedai Warbi. Job Training, majoring in informatics engineering, Pamulang University Campus Supervisor Pandu Wiliantoro S.Kom., M.Kom. Data recording and management as well as ordering transactions at restaurants in several places are still carried out normally. The use of stationery and paper when recording menu orders results in overlapping orders, unordered delivery of orders. Restaurant owners or managers who are far from the location make it difficult to get restaurant information, thus causing data falsification. Web-based food and beverage ordering information system is an application that uses a computerized system. This application can process food menu data, drink menus, report data. This application is made using PHP, HTML and MySQL database. This webbased food and beverage ordering system application can be one solution that can beused.